Clinical Severity of COVID-19 among Pediatric in Tertiary Level Hospital, West Sumatra - Yani, Finny Fitry; Izzah, Amirah Zatil; Alkamdani, Riki; Widoyo, Ratno (Frontiers on Healthcare Research, 2024)
Background: COVID-19 clinical signs can be different for each pediatric patient. This study aims to systematically evaluate the clinical, laboratory examination, severity of COVID-19 infection of pediatric patients in RSUP Dr. M. Djamil General Hospital. Methods: This is a cohort retrospective study. Data were extracted from the medical records of pediatric patient who received COVID-19 medical treatment between September 2020 to June 2021. The data were presented as frequency, percentage and adjusted odd ratio (aOR). Bivariate and multivariate analysis was done to identify the association. Results: The results showed that from a total sample of 93 patients, the majority of these patients were male (60,2%) and fell within the age groups of 1-5 years (30,1%) and 11-15 years (31,2%). Most pediatric patients presented with a mild severity level of COVID-19. Clinical characteristics, such as consciousness (p=0.014), neurologic deficits (p=0.035), and thoracic abnormalities (p=0.040), showed a significant association with the severity level of COVID-19. There are no significant association between laboratory results and the severity level of COVID-19. Admission to PICU was identified as a protective factor against the mortality of COVID-19 (aOR=0.02) and abdominal abnormalities were identified as a contributing factor to mortality among pediatric COVID-19 cases (aOR=14.44). Conclusions: Clinical characteristics including consciousness, neurologic deficits, and thoracic abnormalities were associated with the severity level of COVID-19. PICU admission and abdominal abnormalities were associated with mortality among pediatric COVID-19 patients.